Lineage diversification of pigeon paramyxovirus effect re-emergence potential in chickens - Yee, Ling Chong; Oekyung, Kim; Ross, Mary (BioMed Central, 2014)
Genotype VI-paramyxovirus (GVI-PMV1) is a major cause of epidemic Newcastle-like disease in Columbiformes. This genotype of avian paramyxovirus type 1 has diversified rapidly since its introduction into the US in 1982 resulting in two extant lineages, which have different population growth properties. Although some GVI-PMV1s replicate poorly in chickens, it is possible that variants with different replicative or pathogenic potential in chickens exist among the genetically-diverse GVI-PMV1s strains. To determine if variants of Columbiform GVI-PMV1 with different phylogenetic affiliations have distinct phenotypic properties in chickens, we investigated the replicative properties of 10 naturally circulating pigeon-derived isolates representing four subgroups of GVI-PMV1 in primary chicken lung epithelial cells and in chicken embryos. Our data demonstrate that GVI-PMV1 variants have different infection phenotypes in their chicken source host and that properties reflect subgroup affiliation. These subgroup replicative properties are consistent with observed dynamics of viral population growth.